2022
DOI: 10.1038/s41467-022-28146-6
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling of cocatalysts photodeposited selectively on facets of BiVO4 to boost solar water splitting

Abstract: Bismuth vanadate (BiVO4) has been widely investigated as a photocatalyst or photoanode for solar water splitting, but its activity is hindered by inefficient cocatalysts and limited understanding of the underlying mechanism. Here we demonstrate significantly enhanced water oxidation on the particulate BiVO4 photocatalyst via in situ facet-selective photodeposition of dual-cocatalysts that exist separately as metallic Ir nanoparticles and nanocomposite of FeOOH and CoOOH (denoted as FeCoOx), as revealed by adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
128
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(131 citation statements)
references
References 52 publications
3
128
0
Order By: Relevance
“…Previous studies have mostly focused on the m-BiVO 4 crystals with highly exposed low-index {010} and {110} facets. [23][24][25][26]29 Studies revealed that there are obvious differences in the carrier separation ability, the ability to adsorb reactive molecules and the surface reactivity between {010} and {110} facets, 24,28 which are closely related to the photocatalytic performance. These interesting phenomena inspired us to investigate the physicochemical properties of the low-index {101} facets based on DFT calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have mostly focused on the m-BiVO 4 crystals with highly exposed low-index {010} and {110} facets. [23][24][25][26]29 Studies revealed that there are obvious differences in the carrier separation ability, the ability to adsorb reactive molecules and the surface reactivity between {010} and {110} facets, 24,28 which are closely related to the photocatalytic performance. These interesting phenomena inspired us to investigate the physicochemical properties of the low-index {101} facets based on DFT calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The actual conductive potential of n-type semiconductors is negatively offset by 0.10 eV from the flat charging potential drawn in the figure. 9 Therefore, its conductive potentials are −0.84 eV and −0.68 eV vs. Ag/AgCl (0.20 eV). The conductive potentials were −0.64 eV and −0.48 eV, respectively when they were converted to standard hydrogen electrodes (NHE).…”
Section: Resultsmentioning
confidence: 99%
“…Artificial photosynthesis is a great approach for generating sustainable energy by turning solar energy into chemical energy for storage. 8 Photocatalytic hydrogen evolution is a promising strategy for converting solar energy into hydrogen energy, [9][10][11] which not only can address the energy crisis but also resolve growing ecological threats. Photocatalytic water splitting 12 to generate H 2 relies on the development of high-performance, low-cost photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22] In addition, photocatalyst surface modication with suitable metal or metal oxide co-catalysts has also been widely recognized to accelerate the charge utilization process by fast extraction of photogenerated electrons and holes on the surface for photocatalytic reactions. [23][24][25][26][27][28] Although the anisotropy of semiconductor photocatalysts determines the photogenerated charge separation properties, [29][30][31] the spatial charge separation may also be affected by the surface properties of the semiconductors when pre-treated under acidic or alkaline solutions. For example, the regulation of pH could modulate the surface charge characteristics of SrTiO 3 with anisotropic facets, including the isoelectric point and local surface charge densities, and affect the adsorption of charged ions.…”
mentioning
confidence: 99%